2020
DOI: 10.1111/imr.12924
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between γδTCR signaling and the E protein‐Id axis in γδ T cell development

Abstract: Lymphocytes with innate-like qualities such as γδ T cells, invariant natural killer T cells (iNKT cells), and innate lymphoid cells (ILCs) serve unique and critical roles within the immune system. γδ T cells are widely distributed throughout mucosal and epithelial cell-rich tissues and serve as an important early source of interleukin (IL)-17 under inflammatory conditions. 1,2 γδ T cell subsets share effector programs with CD4 (helper) and CD8 (cytotoxic) T cells, but acquire their functional abilities by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 168 publications
(191 reference statements)
0
12
0
Order By: Relevance
“…The type 3 and type 2 developmental pathways were largely shared but split at the final maturation stage. Overall, based on the expression patterns of TCR-signaling related markers 57 , 96 , 134 , 140 and of the transcription factor PLZF 103 , 110 , 134 , 141 , 142 , we propose that differences in timing and strength in TCR signaling result in associated differences of the transcription factor PLZF that then guides the final thymic γδ effector fate.…”
Section: Discussionmentioning
confidence: 98%
“…The type 3 and type 2 developmental pathways were largely shared but split at the final maturation stage. Overall, based on the expression patterns of TCR-signaling related markers 57 , 96 , 134 , 140 and of the transcription factor PLZF 103 , 110 , 134 , 141 , 142 , we propose that differences in timing and strength in TCR signaling result in associated differences of the transcription factor PLZF that then guides the final thymic γδ effector fate.…”
Section: Discussionmentioning
confidence: 98%
“…Engagement of strong γδ TCR ligands in conjunction with co-stimulatory molecules results in strong TCR signaling and the γδT1 developmental outcome, whereas a less strong TCR signal leads to the γδT17 fate ( 46 48 ). All these lineage choices are intimately associated with the balance between Id3 and E proteins ( 49 , 50 ).…”
Section: Tcr Signal Strength Determines Lineage Outcomes During the I...mentioning
confidence: 99%
“…However, γδTCR‐restricted backgrounds and in vitro culture models showed that loss of Id3 activity predisposes DN3 cells to enter the αβ T cell lineage even when a γδTCR signal is received, revealing the role of Id3 in the αβ/γδ lineage choice (Lauritsen et al, 2009). While periods of TCR signaling followed by transient periods of Id3 expression are essential for T cell development, it is unclear how the balance between E protein and Id3 activity controls E protein target gene expression (Anderson & Selvaratnam, 2020).…”
Section: T Cell Developmentmentioning
confidence: 99%
“…αβ T cells express a TCR composed of TCRα and TCRβ chains and include the conventional “helper” and “killer” T cells that execute the adaptive immune response. γδ T cells express a complex of TCRγ and TCRδ chains which are tightly linked to their functional capabilities (Anderson & Selvaratnam, 2020). γδ T cells perform critical functions, including defense against infection, cancer cell lysis, and maintenance of microbial homeostasis and barrier tissue integrity (Chen et al, 2020; Hovav et al, 2020; Mikulak et al, 2019; Papotto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation